ANALISIS PENCANTUMAN KLAUSULA EKSONERASI DITINJAU DARI ASAS KEBEBASAN BERKONTRAK DI INDONESIA - Mega Indah Fiani (Jurnal Hukum Lex Generalis, 2024)
Article 1338 paragraph (1) of the Civil Code is the basis for the birth of the principle of freedom of contract embraced by every individual who has an agreement as long as the agreement does not violate the conditions of the validity of the agreement. The principle of freedom of contract gives birth to the freedom to add clauses in the agreement called exoneration clauses which relieve the parties of some or all of their responsibilities. The purpose of this study is to analyze the inclusion of the exoneration clause from the principle of freedom of contract in Indonesia and to know the jurisprudence of judges regarding the exoneration clause. This research is processed with a normative juridical approach method, namely by looking at law as a set of regulations as a normative nature (law in book). The results of the problem were found that even though it was based on the principle of freedom of contract, the parties could not make it a way to be able to pressure and act unfairly to other parties, especially weaker parties. There are limits that must be applied by the parties even with the principle of freedom of contract. A court decision regarding the exoneration clause can cancel the agreement if it is considered that the exoneration clause is biased and does not meet the principle of justice for the parties to the agreement.